Conceptual approach for the rehabilitation of former radiation hazardous lands - Miarzlova, Volha А. (Journal of the Belarusian State University. Ecology, 2019)
Various approaches to the use of the concept of rehabilitation are studied. The article presents the author’s interpretation of the rehabilitation of radiation hazardous lands. The conceptual scheme of rehabilitation of radiation hazardous lands is given. It includes the preparatory phase, legal rehabilitation, remediation and radiological remediation. The preparatory phase has an important role to play. The balance of the decision on the return of land depends on its successful implementation. In this regard, the main recommendations on the formation of a strategy for the return of former radiation-hazardous land in agricultural production are given. They include analysis of the needs of land users; consideration of environmental and economic constraints; planning of the guidelines of use and purpose of land. The prerequisites for the return of land are a shortage of arable or meadow land, a shortage of land with low (137 Cs to 185,0 kBq/m2 and 90 Sr to 18,5 kBq/m2) or medium (137 Cs to 555,0 kBq/m2 and 90 Sr to 37,0 kBq/m2) radionuclide contamination, the need for more productive land, the availability of land use adjacent to the returned. For the production of commercial products, it is not eco-nomically feasible to return sites requiring the removal of large shrubs and small forests of different density. The same refers to areas with dense undergrowth and a forest of different density. Priority should be given to the production of products for food purposes, then the production of feed for fattening cattle (for sale in the Customs Union zone), then – feed for milk cow.